Mastering in music - Braddock, John-Paul; Hepworth-Sawyer, Russ; Hodgson, Jay; Shelvock, Matt; Toulson, Rob (Routledge, Taylor & Francis Group, 2021)
"Mastering in Music is a cutting-edge edited collection that offers twenty perspectives on the contexts and process of mastering. This book collects the perspectives of both academics and professionals to discuss recent developments in the field, such as mastering for VR and high resolution mastering, alongside crucial perspectives on fundamental skills, such as the business of mastering, equipment design and audio processing. Including a range of detailed case studies and interviews, Mastering in Music offers a comprehensive overview of the foremost hot topics affecting the industry, making it key reading for students and professionals engaged in music production"--
"A Focal Press book"--from cover
Keywords: Audiotechnik; Musikproduktion; Mastering (Sound recordings); Sound recordings / Production and direction; Aufsatzsammlung